Degree of Conversion of Luting Materials Under CAD/CAM Blocks - DOĞU KAYA, BENGÜ; YILMAZ ATALI, PINAR; ŞENOL, AYŞE ASLI; TARÇIN, BİLGE; KAHRAMANOĞLU, ERKUT (My University, 2023)
Introduction: The aim of this in vitro study was to evaluate the degree of conversion of dual-cured luting cement (Bifix QM, Voco) and flowable composite (GrandioFlow, Voco) under lithium disilicate glass-ceramic (Emax, Ivoclar Vivadent) and hybrid (Grandio Blocs, Voco) CAD/CAM blocks with different thicknesses. Material and Methods: Disc-shaped CAD/CAM blocks with a diameter of 8 mm and two different thicknesses of 1.5 and 2 mm were used in this study. Bifix QM and GrandioFlow (n=3, per material) were polymerized through 1.5- and 2-mm thick CAD/CAM materials. Twenty-four samples with standard thicknesses were achieved by placing 2 adhesive tapes (3M) between the glass plate and mylar strip was used in this set up. The luting cement and flowable composite were polymerized from the upper surface of the blocks using a LED-curing unit (1000 mw/cm2 , Valo Cordless, Ultradent) by closing the periphery. Samples were stored in distilled water at 37°C for 24 hours. Luting materials (100 µm thickness) were examined by Fourier Transform Infrared Spectroscopy (Spectrum Two FT-IR Spectrometer, PerkinElmer) analysis and the degree of conversion (DC) were calculated. Data were analyzed with SPSS V23, One-way Anova and Kruskal Wallis tests with the significance level p<0.05. Results: No significant difference was found in DC between Bifix QM (34.68 ± 13.21; 24.94 ± 1.93) and GrandioFlow (41.33 ± 2.28; 38.07 ± 4.57) when using 1.5 mm Emax (p=0.476) and GrandioSo (p=0.050), respectively. DC of GrandioFlow (37.94 ± 5.33) was significantly higher than Bifix QM (23.36 ± 2.03) with Emax-2 mm (p=0.011). DC of Bifix QM was found to be similar under 1.5 mm (p=0.306) or 2 mm (p=0.051) thicknesses of both Emax and GrandioSo. The difference in DC values of GrandioFlow did not show statistically significance for 1.5 mm and 2 mm thicknesses under GrandioSo and Emax (p=0.275; 0.488, respectively). Conclusion: Within the limitations of this in vitro study, it is important to select the proper luting material considering the structure and thickness of the CAD/CAM restoration, along with manufacturers’ instructions. Keywords: CAD/CAM block, degree of conversion, dual-cure resin cement, flowable composite, lithium dislocate glass-ceramic, luting material, nano-ceramic hybrid
Keywords: CAD/CAM block; degree of conversion; dual-cure resin cement; flowable composite; lithium dislocate glass-ceramic; luting material; nano-ceramic hybrid